THE LABORATORY PERFORMANCE OF HIGH TEMPERATURE FATIGUE OF MODIFIED WASTE PLASTIC-BITUMEN IN ASPHALT CONCRETE - Imam Aschuri; R. Anwar Yamin (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
It is well known that the fatigue cracking occurs at an intermediate temperature of around 20°C and many researchers have carried out the fatigue study to generate fatigue regression at temperatures ranging only from 5°C to 30°C. The purpose of this study is to investigate the high fatigue characteristics of asphalt concrete utilizing waste plastic milk bottle (HDPE) as polymer additive over arange temperature of 20°C to 40°C. Waste plastic (HDPE) was used to modify 60/70 penetration grade bitumen and Its effect on basic bitumen properties was tested over a range of test temperatures. The Marshall stability tests were carried out to determine the optimum bitumen content and optimum HDPE content of asphalt concrete. The optimum HDPE content in binder was found to be 1.5% by weight of binder. The laboratory fatigue test on asphalt concrete with and without waste plastic (HDPE) was evaluated using repeated load tests at 20oC,30oC and 40oC under constant stress mode. Temperatures had a significant effect on fatigue performance, which the fatigue performance of asphalt concrete exhibited better at higher temperature. Test results showed that the fatigue performance in term of fatigue life of asphalt concrete using waste plastic-bitumen blend showed higher than conventional mix at a range of temperatures. Key Words: Modified Bitumen, Waste Plastic, Fatigue Cracking, Asphalt Concrete and High Temperatur